A refined stability result for standing waves of the Schrödinger–Maxwell system. (5th September 2019) - Colin, Mathieu; Watanabe, Tatsuya
Abstract: In this paper, we are interested in standing waves of the nonlinear Schrödinger equation coupled with the Maxwell equation. Our aim is to formulate the orbital stability of standing waves in the full gauge invariant form. For this purpose, we study a new constraint minimization problem.